2011
DOI: 10.1007/s10661-011-2172-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pesticide mixtures on degradation of pendimethalin in soils

Abstract: Most agronomic situations involve a sequence of herbicide, fungicide, and insecticide application. On the other hand, use of pesticidal combinations has become a standard practice in the production of many agricultural crops. One of the most important processes influencing the behavior of a pesticide in the environment is its degradation in soil. It is known that due to several pesticide applications in one vegetation season, the pesticide may be present in mixtures with other pesticides or xenobiotics in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 26 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…For example, White et al (2010) found that fungicide chlorothalonil could significantly suppress the degradation of herbicide metolachlor in soil, and inhibition rate is up to two times. Swarcewicz and Gregorczyk (2012) demonstrated that fungicide mancozeb and mixture with thiamethoxam could significantly inhibit the degradation of herbicide pendimethalin, but metribuzin did not affect the behavior of pendimethalin in soil. Therefore, it is necessary to compare and analyze the behaviors of individual pesticides and combined use in soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, White et al (2010) found that fungicide chlorothalonil could significantly suppress the degradation of herbicide metolachlor in soil, and inhibition rate is up to two times. Swarcewicz and Gregorczyk (2012) demonstrated that fungicide mancozeb and mixture with thiamethoxam could significantly inhibit the degradation of herbicide pendimethalin, but metribuzin did not affect the behavior of pendimethalin in soil. Therefore, it is necessary to compare and analyze the behaviors of individual pesticides and combined use in soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, different pesticides are usually applied simultaneously or one after another for protecting the crop from damage. This pesticide application can often result in a combined contamination of pesticide residues in the soil environment (Swarcewicz and Gregorczyk, 2012). Degradation and adsorption are two important behaviors of pesticides in soil, which are directly related to how long the pesticides remain in the soil and how seriously the pesticide affect soil environment (Arias-Estévez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Affording lower amount of herbicide without diminishing efficiency, controlled release formulation has the advantage of being far safer to handle than other pesticide formulations. [25][26][27][28] To the best of our knowledge, selected herbicide model pendimethalin -a pre-emergence innately poisonous selective herbicide -has never been encapsulated before ever within dendritic PAMAM-based novel polyurea microcapsules possessing free reactive functional group. Objective set for the present work was to develop PAMAM-based novel polymeric shell material for efficient release rate of encapsulated core via micro encapsulation using interfacial polymerization technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential interactions between herbicides when compared with the application of each herbicide alone were not fully investigated. Many interactions are possible, including those related to changes in the amount and species diversity of the microbial population from different soils, effects on the specific enzymatic reactions, or those related to physical and chemical effects, such as competition for sorption sites, which interfere directly with leaching [14,15].…”
Section: Introductionmentioning
confidence: 99%